(untitled) (Indian Journal of Arid Horticulture, 2021)
Five pomegranate varieties (Ganesh, Mridula, Bhagwa, Ruby and Jalore Seedless) were evaluated for vegetative and quality parameters for consecutive seven years under at Horticulture Research Station, Anantapur. Jalore Seedless (check) recorded significantly highest values for plant height (2.99 m), no. of stems per plant (5.25) and plant spread (2.64 m EW 2.5lm NS). Among all the varieties, fruit yield per plant and per hectare was highest in Bhagwa (19.13 kgand11.96 t) with fruit weight of 305.21g, total aril weight (168.05g) and 100 aril weight (35.35 g) TSS of 7.87°Brix. Bhagwa was best performer as compared to other popular varieties like Ganesh, Mridula, Ruby and Jalore Seedless. Therefore, on the basis of plant growth and fruit quality attributes variety Bhagwa is recommended for arid regions of Andhra Pradesh.